How can schistosome circulating antigen assays be best applied for diagnosing male genital schistosomiasis (MGS): an appraisal using exemplar MGS cases from a longitudinal cohort study among fishermen on the south shoreline of Lake Malawi. Issue 14 (23rd September 2019) - Kayuni, S. A.; Corstjens, P. L. A. M.; LaCourse, E. J.; Bartlett, K. E.; Fawcett, J.; Shaw, A.; Makaula, P.; Lampiao, F.; Juziwelo, L.; de Dood, C. J.; Hoekstra, P. T.; Verweij, J. J.; et al.
Abstract: We provide an update on diagnostic methods for the detection of urogenital schistosomiasis (UGS) in men and highlight that satisfactory urine-antigen diagnostics for UGS lag much behind that for intestinal schistosomiasis, where application of a urine-based point-of-care strip assay, the circulating cathodic antigen (CCA) test, is now advocated. Making specific reference to male genital schistosomiasis (MGS), we place greater emphasis on parasitological detection methods and clinical assessment of internal genitalia with ultrasonography. Unlike the advances made in defining a clinical standard protocol for female genital schistosomiasis, MGS remains inadequately defined. Whilst urine filtration with microscopic examination for ova of Schistosoma haematobium is a convenient but error-prone proxy of MGS, we describe a novel low-cost sampling and direct visualization method for the enumeration of ova in semen. Using exemplar clinical cases of MGS from our longitudinal cohort study among fishermen along the shoreline of Lake Malawi, the portfolio of diagnostic needs is appraised including: the use of symptomatology questionnaires, urine analysis (egg count and CCA measurement), semen analysis (egg count, circulating anodic antigen measurement and real-time polymerase chain reaction analysis) alongside clinical assessment with portable ultrasonography.